GridVigil: Tri-securing Critical Infrastructure of energy transmission systems through People, Process and Technology - Gadhvi, Hardik; Grid, Ranmuktey (Journal of Advanced Research in Electronics Engineering and Technology; Vol 12 No 1&2 (2025): Journal of Advanced Research in Electronics Engineering and Technology, 2025)
The increasing digitisation of India’s power transmission sector— driven by the integration of SCADA systems, digital substations, and wide-area monitoring—has introduced new vulnerabilities in the critical infrastructure landscape. As threats evolve in complexity and frequency, ensuring cyber resilience has become a strategic imperative. This research evaluates the cybersecurity posture of India’s transmission utilities using the People–Process–Technology (PPT) framework. Drawing on regulatory mandates, case studies, and national and international standards (CEA Guidelines, IEC 62443, NIST SP 800-82), the study identifies significant implementation gaps across organisational capacity, operational governance, and technological deployment. Key findings reveal that utilities with dedicated OT-trained personnel, well-documented response procedures, and active SOC infrastructure demonstrate markedly better threat readiness and response metrics. The paper recommends targeted interventions, including mandatory certifications, red-team simulations, CEA guidelines-compliant procurement, and centralised threat intelligence sharing. The study concludes that cybersecurity in India’s power grid must evolve from a compliance exercise to a performance-driven paradigm, where harmonised policy enforcement, skilled human capital, and resilient architecture collectively safeguard national energy security.